The Strategic Approach of Managing Healthcare Data Exchange in Austria - Duftschmid, G.; Wrba, T.; Gall, W.; Dorda, W. (Methods of Information in Medicine, 2004)
Objectives: The exchange of electronic medical data between healthcare providers constitutes an integral part of modern medicine, and its importance is growing. Efficient application on a national level requires a uniform approach to the management of healthcare data exchange, avoiding isolated solutions that are expensive and also incompatible.Methods: In this communication we explain the basic concepts of establishing a nationwide framework to guide healthcare data exchange in Austria. To achieve this goal, a three-step approach was adopted: (i) creating general guidelines to direct electronic medical data exchange; (ii) defining detailed standards for electronic messages; (iii) organizing pilot projects to implement these standards, and further improving the general guidelines based on the results of the pilot projects.Results: We present the MAGDA-LENA framework which guides healthcare data exchange in Austria, and compare it with the US framework HIPAA. We describe several communication scenarios for which concrete message standards were developed in recent years, based on the MAGDA-LENA framework. We further discuss the implementation of these standards in four pilot projects.Conclusions: The strategic approach of managing healthcare data exchange presented in this paper is expected to have a substantial impact on medical informatics in Austria over the next few years.
Keywords: Computer communication networks; telemedicine; policy making; Health Insurance Portability and Accountability Act (HIPAA)